O processo de tornar-se cuidador principal do paciente renal crônico em hemodiálise - Borges, Verônica Alves (2009)
The process of becoming the main caregiver of the renal chronic hemodialysis patient was pursued by means of a qualitative investigation, which was made upon the results got from 8 female, adult participants above 19 years old, who were family bounds to the patients and to who were in charge of taking care of them. The main caregiver remains invisible to the public politics, for there are not any programs that cover such audience in Brazil. Private initiatives try to provide the creation of support groups; however, there are not enough groups to cover such a huge demand for them. The data have been collected by means of a semistructured interview containing questions that were shaped according to the validated version of the Burden Interview scale (SCAZUFCA, 2002) and of the Maslach s Burnout Inventory - Human Services Survey (MASLACH & LEITER, 1997), in a Brazilian validated version (CARLOTTO & CÂMARA, 2007). The analysis of those data was made based on the Attachment Theory by John Bowlby, and it shows that there is a great positive impact (such as daily routine, health, social common family living, job, finance), as well as a subjective impact (mental stress) acting upon the life of the caregiver. Besides, the burnout syndrome might be considered as a helpful diagnosis for the set of symptoms reported by the main caregiver of the renal chronic patient. Further studies are necessary in order to increase the knowledge concerning the burnout syndrome on the caregivers of renal chronic patients, for each disease demands proper, individual responses concerning the care-giving